Low-wage mobility in the Portuguese labour market - Vieira, José A. Cabral (2018)
Low-wage employment has become a matter of concern in many coun- tries, Portugal being among them. In particular, the extent to which low-wage employment is a permanent or transitory situation is an important issue. This paper examines low-wage mobility in the Portuguese labour market using the bivariate probit model proposed by van de Ven and van Praag (1981), in order to account for the potential endogeneity of the initial state. For this purpose, we use a matched employer-employee panel data for 1996 and 2000. Raw figures show that a signif- icant number of workers are trapped into low-wage employment. We also find that males and the better-educated are more likely to escape from such a situation. Fur- thermore, initial firm characteristics, such as firm size, age and industry influence mobility. In particular, low-wage workers in larger or in newer firms have better mobility prospects.